Subtype specific biomarkers associated with chemoresistance in epithelial ovarian cancer - Abhilash Deo; Souvik Mukherjee; Bharat Rekhi; Pritha Ray (Wolters Kluwer Medknow Publications, 2020)
In spite of the advent of many high throughput technologies, tumor tissue biomarkers are still the gold standard for diagnosis and prognosis of different malignancies including epithelial ovarian cancer (EOC). EOC is a heterogeneous disease comprised of five major subtypes which show distinct clinicopathological features and therapy response. Acquirement of chemoresistance toward therapy is a major challenge for successful treatment outcome in EOC patients. Several markers have been tested by immunohistochemical method to evaluate their prognostic merit to predict clinical outcome. However, a vast majority of such markers have been assessed for high-grade serous and clear cell ovarian cancer, among all subtypes of EOC. The current review elaborates upon those biomarkers that can potentially predict chemoresistance with subtype specificity.